Diseño de un sistema de alimentación Eléctrica para el respaldo parcial de Iluminación de una vivienda (2021)
This project was designed to provide solar energy alternatives to a house in the urban sector of the city of Villavicencio. The use of renewable energy offers economic and environmental advantages to the community, since it proposes a possible solution to a problem related to failures in the electricity supply offered by EMSA.